DETERMINANTS OF THE USE OF BRI INTERNET BANKING ADOPTION: A STUDY ON POLITEKNIK NEGERI SEMARANG STUDENTS - Maycherles, Cindy; Muslikh, Moh (KEUNIS, 2021)
The purposes of this research are to analyze and obtain empirical evidence on the effect of usefulness perception, ease perception, and risk perception toward the use of BRI Internet banking in (Politeknik Negeri Semarang) Polines students both simultaneously and partially. The population of this research was Polines students of all departments from 2017 to 2019 as customers of BRI Internet banking users with a sample of 87 respondents. The research used primary and secondary data. The data analysis model uses the Multiple Linear Regression Analysis Model while the data analysis technique uses F Test, t Test, and R2 Test. The results of the discussion analysis shows that the variables of usefulness perception and ease perception have a significant effect toward the use of Internet banking while variable of risk perception has no significant effect toward the use of Internet banking.